Pengaruh Kualitas Sistem dan Kualitas Informasi Terhadap Kepuasaan Pengguna Enterprise Resource Planning-System Application and Product In Data Processing (ERP-SAP) dengan Perceived Usefulness sebagai Variabel Moderating pada Pelindo I ( Persero) Sumatera Utara - Sigalingging, Eni Duwita; Permatasari, Dina Indah (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
The objective of the research was to find out the influence system quality and information quality on the satisfaction of the users of ERP-SAP (Enterprise Resource Planning-System Application and Product in Data Processing) with Perceived Usefulness as Moderating Variable at PELINDO 1 (Persero) Sumatera Utara. The research used causal method. The samples were 110 respondents, taken by using census technique. Questionnaires were distributed to practice employees who used ERP-SAP PELINDO 1 (Persero) Sumatera Utara. Primary data were obtained from the result of the questionnaires. Hypothesis was tested by using causal correlation test with SEM program and moderating test by using interactive test. The result of the research showed that system quality and information quality had positive and significant influence on the satisfaction of SAP users. Perceived usefulness as moderating variable was not significant in moderating the influence of system quality and information quality on the satisfaction of SAP users.